The Analysis of Students' Difficulties in Speaking English through Voice Note - Prayudha.S, Joko (Foremost Journal, 2023)
The role of technology in the world of education cannot be separated because technology is actually the result of education and learning process. The use of technology becomes a support in the implementation of a success in teaching and learning activities. One of the technologies that can be used in learning English is to use a platform or voice note feature. Therefore, this study examines students' difficulties in learning English through voice note technology. The method used in this research is qualitative using a descriptive approach. Data were obtained through observation and interviews related to students' problems and obstacles in speaking skills using voice notes. The data were analyzed in a descriptive way by following the stages of data reduction, data display and conclusion. The results showed that students' difficulties in speaking skills were divided into two, namely internal and external. Internal factors include lack of self-confidence, courage, inspector, lack of understanding of English vocabulary. While external factors include technological sophistication, internet quota, learning resources or references.